2017
DOI: 10.1038/s41388-017-0046-6
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of autophagy in hallmarks of cancer

Abstract: Evolutionarily conserved across eukaryotic cells, macroautophagy (herein autophagy) is an intracellular catabolic degradative process targeting damaged and superfluous cellular proteins, organelles, and other cytoplasmic components. Mechanistically, it involves formation of double-membrane vesicles called autophagosomes that capture cytosolic cargo and deliver it to lysosomes, wherein the breakdown products are eventually recycled back to the cytoplasm. Dysregulation of autophagy often results in various disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
381
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 458 publications
(393 citation statements)
references
References 122 publications
8
381
0
4
Order By: Relevance
“…These data suggest that up‐regulation of FUNDC1 expression is required for and benefits the late stage of tumor development. It is thus proposed that mitophagy, a selective form of macroautophagy, has dual roles in cancer . Our findings are consistent with the established dual role of general autophagy in cancer.…”
Section: Discussionsupporting
confidence: 91%
“…These data suggest that up‐regulation of FUNDC1 expression is required for and benefits the late stage of tumor development. It is thus proposed that mitophagy, a selective form of macroautophagy, has dual roles in cancer . Our findings are consistent with the established dual role of general autophagy in cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies support the idea that, in established tumors, constitutive autophagy may have a protective role in cancer cells by removing damaged organelles or recycling misfolded macromolecules [47]. In support of this hypothesis, several studies report that autophagy tries to fulfill the high metabolic demands of the proliferating tumor cells exposed to stressful conditions, such as nutrient deprivation, oxidative stress, hypoxia, or in response to therapy [46, 48].…”
Section: Macroautophagymentioning
confidence: 92%
“…In this sense, there are a variety of examples showing that autophagy inhibitors, when used in combination with anticancer drugs, may sensitize chemoresistant cells, thus inhibiting tumor survival [47, 71]. For example, it has been reported that inhibition of autophagy function by depletion of Atg5, Atg7 or beclin1 may revert the acquired resistance against tamoxifen in HER-positive breast cancer cells [72].…”
Section: Macroautophagymentioning
confidence: 99%
“…7,8 Autophagy is a highly conserved physiological process that results in the turnover of intracellular material, allowing the cells to remain stable under the stimuli of some stress factors. 10 However, the role and underlying mechanisms of starvation-induced autophagy in the invasion and migration of urinary bladder cancer cells are largely unknown. 10 However, the role and underlying mechanisms of starvation-induced autophagy in the invasion and migration of urinary bladder cancer cells are largely unknown.…”
Section: Introductionmentioning
confidence: 99%